Hexacopter Drones for Fertilizer Sowing in the Agricultural Sector Using the Global Positioning System (GPS) - Satyo Nuryadi; Zulkhairi; Rodhiyah Mardhiyyah; Bayu Ari Pratama (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2021)
Indonesian agricultural products are one of the highest-yielding agricultural commodities on the Asian continent. Farmers are still reliant on a manual method to agricultural land care and management, one of which is the application of fertilizer to agricultural land. As a result, with the help of an unmanned aerial vehicle (UAV) or a robot flying drone, a system or fertilizer sowing equipment is utilized on plants. The results of this study led to the creation of a hexacopter drone equipped with fertilizer-based sensors and GPS. Hexacopter refers to a quadcopter having only four rotors. Drone rides are paired with tank-shaped sower actuators and fertilizer spraying as a container and fertilizer sowing method. Using GPS sensor block m8n, which serves as a satellite signal receiver and is converted to a position point in the form of longitude and latitude values, the vehicle can travel to fertilize by following the route of the coordinate point that has been identified in the agricultural land region. The Pixhawk 2.4.8 flight control system, which uses automatic or autonomous controls, can run smoothly, allowing the ride to automatically seed the track. The Lippo 2300mAh 4s battery has a maximum ride load lifting capability of 500 grams of fertilizer and a fertilizing height of three meters.